2022
DOI: 10.3389/fnut.2022.1025080
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of ginkgo biloba kernel juice using Lactobacillus plantarum Y2 from the ginkgo peel: Fermentation characteristics and evolution of phenolic profiles, antioxidant activities in vitro, and volatile flavor compounds

Abstract: In this study, a strain of Lactobacillus plantarum Y2 was isolated from the ginkgo peel, and showed adequate adaptation to the ginkgo biloba kernel juice. After 48 h of fermentation, the number of viable cells in the stable growth phase was remained at 10.0 Log CFU/mL, while the content of total organic acid increased by 5.86%. Phenolic substances were significantly enriched, and the content of total phenolic substances increased by 9.72%, and the content of total flavonoids after fermentation exceeded 55.33 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…L. plantarum Y2 was previously isolated from the surface of Ginkgo biloba kernels through screening and then stored at −20 °C [8] . To obtain primary inoculum, Ginkgo biloba kernels were inoculated in MRS medium at a ratio of 1:1.5 (g: mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…L. plantarum Y2 was previously isolated from the surface of Ginkgo biloba kernels through screening and then stored at −20 °C [8] . To obtain primary inoculum, Ginkgo biloba kernels were inoculated in MRS medium at a ratio of 1:1.5 (g: mL).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain a comprehensive understanding, it is necessary to conduct a comparative analysis encompassing microbial growth, carbohydrate and protein profiles, organic acids, volatile compounds, and phenolic compounds. In our previous study, it was demonstrated that the antioxidant and antibacterial activities of fermentation samples with L. plantarum could be observably improved, while the content of MPN was decreased [8] . However, there is still much space for improvement in terms of the fermentation capacity of L. plantarum , nutrient utilization, degradation of toxic substances, and flavor enhancement.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fruit and vegetable juices fermented with probiotics have nutritional and health functions. ( Yang et al, 2022 , Yang et al, 2022 ) fermented silver almond juice with Lactobacillus acidophilus , Lactobacillus plantarum and Lactobacillus paracei . The number of lactic acid bacteria in silver almond juice reached over 8.0 log CFU/ml, the content of terpenolactone increased 1.6-fold, the total amount of phenolic substances increased by about 9 %, and the ability of ABTS to scavenge free radicals increased by 35.3 %∼39.8 % can effectively inhibit the growth of pathogenic bacteria such as Escherichia coli .…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…However, it is challenging to ensure the above requirements. In recent years, some researchers have found that adding an appropriate amount of prebiotics can have a symbiotic effect with probiotics, thus maintaining a high number of viable bacteria in probiotic beverages and improving their sensory quality, physical and chemical properties ( Yang et al, 2022 , Yang et al, 2022 ).…”
Section: The Improvement Effect Of Probiotics On Fruit and Vegetable ...mentioning
confidence: 99%